Supplementary Figure S1 from Randomized Trial of Tepotinib Plus Gefitinib versus Chemotherapy in EGFR-Mutant NSCLC with EGFR Inhibitor Resistance Due to MET Amplification: INSIGHT Final Analysis - Chong Kin Liam (15331321) (2025)
Outcomes of treatment for all individuals enrolled